Steppe Dreams : Time, Mediation, and Postsocialist Celebrations in Kazakhstan - Adams, Margarethe (Central Eurasia in context., 2020)
Steppe Dreams concerns the political significance of temporality in Kazakhstan, as manifested in public events and performances, and its reverberating effects in the personal lives of Kazakhstanis. Like many holidays in the post-Soviet sphere, public celebrations in Kazakhstan often reflect multiple temporal framings--utopian visions of the future, or romanticized views of the past--which throw light on present-day politics of identity. Adams examines the political, public aspects of temporality and the personal and emotional aspects of these events, providing a view into how time, mighty and unstoppable, is experienced in Kazakhstan.